2022
DOI: 10.31083/j.ceog4904088
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive surgery in gynecological cancers: update and systematic review

Abstract: Introduction:In the last decades, the introduction of laparoscopy and, more recently, of robotic surgery, offered new options for surgical treatment also in gynecological malignancies, as an alternative to open surgery. When considering the best surgical treatment option for gynecological malignancies, evidence about safety, feasibility, and oncological outcomes must be taken into account, to offer the best treatment to the patient. The present review aims to provide an updated scenario over the available evid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 99 publications
(236 reference statements)
0
1
0
Order By: Relevance
“…These results demonstrated that RPRS can be valid surgical modality for myomectomy. There are number of research results showing that MIS and single-site robotic surgery are useful in various surgeries related to gynecological cancer [13,14]. However, in uterine myomectomy, the application of MIS is particularly difficult because firm grasp and strong pulling are required during surgery.…”
Section: Discussionmentioning
confidence: 99%
“…These results demonstrated that RPRS can be valid surgical modality for myomectomy. There are number of research results showing that MIS and single-site robotic surgery are useful in various surgeries related to gynecological cancer [13,14]. However, in uterine myomectomy, the application of MIS is particularly difficult because firm grasp and strong pulling are required during surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Over the last decade, the burden of cancer incidence as well as mortality has grown rapidly worldwide and is reflected in the rates of gynaecological cancer increase, with cervical and uterine cancer incidence and mortality being the seventh most common cancers in women [5]. With the increasing rates of GO operations, especially technically challenging minimally invasive surgery (MIS) [6,7] in obese patients and patients with multiple comorbidities, it is even more important to be able to accurately predict the likelihood of perioperative complications and involve patients in joint decision-making about their surgery. Iyer et al were able to demonstrate, in their prospective multi-centre study, that the intraoperative rate of complications amongst patients undergoing surgery for cancer was 5.4%, whereas the postoperative complications rate was 27.1% [8].…”
Section: Introductionmentioning
confidence: 99%